Hypervelocity impact flash expansion geometry under various spacecraft surface electrical conditions. (April 2021) - Hew, Y.M.; Close, S.
Highlights: Impact surface electrical condition has a statistically significant influence on the impact flash expansion geometry. Impact flash originates from and is connected to the impact plasma properties. Strong similarity between the impact plasma and flash expansion geometry. First impact flash expansion geometry characterization under various impact surface electrical conditions in a collisionless environment. Abstract: A more congested space environment due to increasing space activities introduces new threats to spacecraft operators. Among these threats include hypervelocity impacts from microparticles ( < 1  µg) in the form of meteoroids and space debris. These microparticles travel at speeds between 11.2 and 72.8 km/s with respect to the Earth and can impact spacecraft forming a small ( ∼ 1  µm) and dense ( ∼ 10 26  m − 3 ) plasma. This plasma can generate a strong optical emission (impact flash) and a radio frequency (RF) emission. These emissions can lead to spacecraft electrical anomalies when the impacted spacecraft surface (target) carries high electrical potential due to various space weather effects. To understand the microparticle hypervelocity impact plasma and its associated threat to spacecraft electronics, we studied the hypervelocity impact flash expansion geometry under various spacecraft surface electrical conditions. Three high-speed broadband photomultiplier tubes (PMT) are used to capture the temporal evolution of the impact flash and the temporal evolution of the angular distribution of the impact flash expansion geometry in a 3 MV electrostatic dust accelerator during a ground-based experiment. Results indicate that the impact surface electrical condition has a statistically significant influence on the impact flash geometry, and a strong similarity between the impact plasma and flash expansion geometry. Thus, this paper provides new experimental support for the impact flash origin from and connection with the impact plasma, and serves as the first impact flash expansion geometry characterization under various impact surface electrical conditions in a collisionless environment ( < 10 − 5  Torr).